Triaging in Pulmonary Embolism - Sanchez, Olivier; Planquette, Benjamin; Roux, Antoine; Gosset-Woimant, Marine; Meyer, Guy (Seminars in Respiratory and Critical Care Medicine, 2012)
Risk stratification of patients with pulmonary embolism represents an important step and may help to guide initial therapeutic management. Pulmonary embolism can be stratified into several groups, with different risk of early death or complications based on the presence of several risk factors. High-risk pulmonary embolism is defined by shock or peripheral signs of hypoperfusion. It is a life-threatening emergency with high short-term mortality (>25%) requiring specific therapeutic strategy with inotropic agents and fibrinolysis. In normotensive patients with pulmonary embolism, the presence of right ventricular dysfunction assessed by echocardiography or myocardial injury based on elevated levels of biomarkers, is associated with an intermediate risk of early death. These patients require close monitoring, and the role of thrombolytic treatment is currently assessed in a large trial. Lastly, patients with normotensive pulmonary embolism and without right ventricular dysfunction or myocardial injury have a low risk of death and complications. These patients may be candidates for home treatment. Several scores combining these risk factors have been described.
Keywords: pulmonary embolism; risk stratification; predicting prognosis; right ventricular failure; troponin; brain natriuretic peptide (BNP)